Determination of Parity Price for Gas and Electricity in Terms of Estimation of Household Incomes and Energy Costs - Pysar, Nadiia; Dergacheva, Victoria (International Journal of Energy Economics and Policy, 2018)
The paper is concerned with comparing household incomes in Ukraine and European countries, estimating households' gas and electricity costs, as well as determining parity prices for these goods in Ukraine for 2016. The calculation of parity prices for electricity and gas was carried out by the share of household's electricity and gas costs in the respective country to its income level and by the absolute need of the corresponding household for electricity and gas in the respective country. The determination of the parity price for gas and electricity relative to household incomes and energy costs is an attempt to come up with a decision on the need to increase or decrease prices for these goods in Ukraine compared to other countries and to assess their relationship to household incomes in order to avoid fuel poverty in Ukraine. An investigation of this problem enables to focus on comparing prices and electricity and gas costs with household incomes using a sales comparison approach and determine the need to increase or decrease prices in Ukraine to the level of European prices for similar goods. This approach to determining the parity price for energy resources can be used for any other country taken as a basis for analysis and calculation. Keywords: energy efficiency, pricing, parity, law of one price, market conditions, liberalization, common energy space. JEL Classifications: B41, R13, O15, N3.